2003
DOI: 10.2337/diacare.26.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes as a Predictor of Change in Functional Status Among Older Mexican Americans

Abstract: OBJECTIVE -Epidemiological studies have demonstrated that older Mexican Americans are at high risk for type 2 diabetes and its complications. Type 2 diabetes leads to a more rapid decline in functional status among older Mexican Americans with diabetes. This study was designed to examine the impact of diabetes on change in self-reported functional status over a 2-year period among older Mexican Americans with diabetes. RESEARCH DESIGN AND METHODS -We performed a longitudinal analysis with repeated measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 22 publications
5
67
0
Order By: Relevance
“…Over the past decade, there has been increasing focus on the influence of diabetes on functional limitations in middle-aged and older adults [1][2][3][4][5][6][7][8][9][10][11][12][13]. Although findings from these studies were not consistent in reporting which aspects of physical function were most affected by diabetessome studies report that diabetes was associated with increased rates of functional declines in instrumental activities of daily living, strength, and mobility, but not with activities of daily living [12], whereas others have found the strong link between diabetes and limitations in activities of daily living [6,11]-these studies have generally shown that diabetes confers a markedly increased risk of functional limitations in middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been increasing focus on the influence of diabetes on functional limitations in middle-aged and older adults [1][2][3][4][5][6][7][8][9][10][11][12][13]. Although findings from these studies were not consistent in reporting which aspects of physical function were most affected by diabetessome studies report that diabetes was associated with increased rates of functional declines in instrumental activities of daily living, strength, and mobility, but not with activities of daily living [12], whereas others have found the strong link between diabetes and limitations in activities of daily living [6,11]-these studies have generally shown that diabetes confers a markedly increased risk of functional limitations in middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that persons with diabetes mellitus have greater functional decline than other older persons [59][60][61][62][63][64]. Persons with diabetes are much less likely to read, garden, use the telephone, write letters or go out socially [65].…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…On querying about the expectations of the elderly with type II diabetes, the answer obtained was that the patients wanted to primarily and independently fulfill the ADL (26). Wu et al (27) compared the performance of ADL in healthy individuals with that of the diabetics and found that more than 74% of the diabetics had a disability in performing the basic ADL, and that more than 50% had a disability in performing the instrumental ADL. In a study conducted in the United States, it was indicated that 79.1% elderly were found to be independent in the ADL.…”
Section: Discussionmentioning
confidence: 99%